Elements of Anime Style in the Illustrative Works of Senbazuru Art Course Participants, Yogyakarta - Dimas Afrillio Caesar Nugraha; Eko Sugiarto (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Although Indonesia's distinctive illustration style continues to evolve, anime's visual aesthetic has become one of the most dominant styles among young illustrators. This study explores how anime aesthetics are adapted and expressed in the illustration works of participants at the Senbazuru course center in Yogyakarta and how anime motivates their creative process. A qualitative case study design was used to collect data through observation, interviews, and documentation of works, which was then analyzed. The results show that participants' works display distinctive anime aesthetic characteristics, such as expressive large eyes, simplified faces, and unnatural hair colors. They also incorporate Japanese visual symbols, such as school uniforms and cherry blossoms, in both fan art and original characters. This visual adaptation transforms the anime style according to each individual's personal style, rather than merely imitating it. From a motivational perspective, anime serves as the initial trigger and sustained driving force in the participants' creative process. External factors from community and social environment, combined with internal factors such as personal interest and satisfaction in creating art, form a mutually reinforcing cycle of motivation. As a non-formal education center, the Senbazuru Art Studio facilitates growth in creativity rooted in personal interests and popular culture. By supporting the adaptation of anime aesthetics and encouraging individual expression, the studio plays a crucial role in shaping the visual identity of Indonesia's youth.